Assessing critical indicators of supply chain ambidexterity in the 3PL industry: Insights from Indonesia - Rafsanjani, Hasemy; Vanany, Iwan (Universitas Mercu Buana, 2025)
Supply chain ambidexterity (SCX) is essential strategy for enhancing the competitiveness and business continuity of third-party logistics (3PL) companies in Indonesia. SCX combines the approaches of Supply Chain (SC) agility and SC integration simultaneously to foster business performance. However, research on the factors influencing SCX remains limited. This study integrated the Fuzzy Delphi Method (FDM) to validate 41 proposed indicators and applied Best-Worst Method (BWM) to assess the relative weight and examine the most and least effective indicators for Indonesia’s 3PL industry. The findings revealed 17 effective indicators, with the top 5 being SC sensing, adaptability, process optimization, regulatory compliance, and employee competency development, which were identified as the most significant indicators. These indicators are critical drivers that ensure the successful implementation of SCX strategy. The results offer valuable insights to professionals and policymakers, helping them formulate strategies to strengthen ambidextrous capabilities in the dynamic environment of the 3PL sector, thereby contributing to a more sustainable and competitive logistics landscape in Indonesia.